The Value Semantics in “Intelligent Travel” Discourse - O. V. Ramantova (Дискурс, 2021)
Introduction. The present paper aims at describing the results of researching the axiological aspect of the category “intelligent travel” functioning in the English language travel discourse. The relevance of the research is defined, firstly, by continuously developing tourist industry and the emergence of new tourist concepts which are embodied in numerous travel editions and, secondly, by insufficient knowledge of axiological aspect of certain travel-genres. The research is completed within the anthropooriented paradigm of linguistic studies and thus contributes to the development of this approach. The novelty of the study lies in revealing specific values represented in intelligent travel-texts and forming a special value line.Methodology and sources. The research is based on the English language texts about travelling. National Geographic was used as the main source of material. For the selection of travel texts, the continuously sampling method was used. The general methodology of studying the “intelligent/slow travel” concept also includes the method of semantic analysis, the method of semantic-stylistic analysis, elements of communicative-pragmatic analysis.Results and discussion. The results of the study include the description of the content of the intelligent travel category, the review of existing types of values, and the description of basic meanings forming the value picture of the world in travel-texts of this genre – sensory values, aesthetic values, morally-ethical and rationalistic value meanings. Within this research it is important to consider “anti-value” which is represented predominantly in texts about wildlife conservation and which enhances the pragmatic impact of the text on the reader. The result of the study is the conclusion about certain language specific of the category of intelligent travelling which is actualized through special value prism.Conclusion. The study reveals the specificity of the value paradigm of slow/intelligent travel texts. The semantic space of texts about intelligent travelling is filled with certain value markers in total constructing the value picture of the world through the prism o f which the travelling and experiencing author expresses not only his own vision of things, but the moral side of life aspects. The chosen methodology can be applied for further research and similar studies of other genres of travel-discourse.